Identification of Trypanosoma cruzi Polyamine Transport Inhibitors by Computational Drug Repurposing - Reigada, Chantal; Sayé, Melisa; Phanstiel, Otto; Valera-Vera, Edward; Miranda, Mariana R.; Pereira, Claudio A. (Frontiers in Medicine, 2019)
Trypanosoma cruzi is the causative agent of Chagas disease, a parasitic infection endemic in Latin America. In T. cruzi the transport of polyamines is essential because this organism is unable to synthesize these compounds de novo. Therefore, the uptake of polyamines from the extracellular medium is critical for survival of the parasite. The anthracene-putrescine conjugate Ant4 was first designed as a polyamine transport probe in cancer cells. Ant4 was also found to inhibit the polyamine transport system and produced a strong trypanocidal effect in T. cruzi. Considering that Ant4 is not currently approved by the FDA, in this work we performed computer simulations to find trypanocidal drugs approved for use in humans that have structures and activities similar to Ant4. Through a similarity ligand-based virtual screening using Ant4 as reference molecule, four possible inhibitors of polyamine transport were found. Three of them, promazine, chlorpromazine and clomipramine, showed to be effective inhibitors of putrescine uptake, and also revealed a trypanocidal activity in epimastigotes (IC50 values of 69.0, 50.8 and 49.4 μM, respectively) and trypomastigotes (IC50 values of 3.5, 2.8 and 1.4 μM, respectively). Finally, molecular docking simulations suggest that the interactions between the T. cruzi polyamine transporter TcPAT12 and all the identified inhibitors occur in the same region of the protein. However, this location is different from the site occupied by the natural substrates. The value of this effort is that repurposing known drugs in the treatment of other pathologies, especially neglected diseases such as Chagas disease, significantly decreases the time and economic cost of implementation.